Back to Basics: Flexible Endoscope Processing. (27th April 2016) - Spruce, Lisa
Abstract: Flexible endoscopes are important tools in patient care, yet recent outbreaks of infections in patients who have undergone endoscopic procedures have increased awareness of how the complex design of these instruments makes them difficult to clean. This Back to Basics article focuses on flexible endoscope processing and provides sterile processing, endoscopy, and perioperative team members with strategies for successful processing of these instruments.